Aquatic and palustrine plants of restinga in a Ramsar site in the easternmost Amazon, Brazil - N. P. F. Alves; M. C. A. Pestana; S. F. Pires; J. C. A. Penha; V. R. Cardoso-Neto; A. V. Scatigna; R. V. C. Saraiva (Brazilian Journal of Biology)
Abstract Aquatic and palustrine plants are a group of plants that have morphological and anatomical adaptations to occupy permanent or temporary aquatic environments. In this study, we carried out the first floristic survey of aquatic and palustrine plants in restingas (restinga swamps and swamp forests) of a Ramsar site in the municipality of Guimarães, western coast of Maranhão State and easternmost Amazon, Brazil. In total, 52 species of 43 genera and 28 families were collected between July 2022 and October 2023, during the dry and rainy seasons. Voyria aphylla (Jacq.) Pers. is a new record for Maranhão. Melastomataceae (9 spp.) was the most representative family, followed by Fabaceae and Plantaginaceae (4 spp. each). Palustrine and emergent plants accounted for 58% and 31% of the species richness, respectively. This study adds important information for local and national policies to ensure biodiversity conservation of the plant biodiversity in Maranhão’s coastal ecosystems.